Bridging the Community and Police Divide through the Planning Table - Kyle Znamenak (Adult Education Research Conference, 2019)
This roundtable highlights how an urban higher education institution used its capital to develop a police training program that met the needs of the police departments and communities they serve.
Keywords: continuing education; police training; planning table; higher education